Meningkatkan Keterampilan Berwudhu Melalui Model Pembelajaran Discovery Learning Berbantuan Vitara Berwudhu Pada Siswa Kelas Vii-1 Smp Negeri 13 Langsa Tahun Ajaran 2022/2023 - mariadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to obtain an overview of improving ablution skills through the Discovery Learning learning model for students in PAI learning class VII SMP Negeri 13 Langsa. This study used a classroom action research design which was carried out in two stages, cycle I and cycle II. Data collection is done by assessment or performance. Based on management data, it is known that at the pre-cycle stage of the skills training skills for ablution, students in class VII-2 have a percentage of 69.85% with the acquisition of skills > 75 by 10% (2 students) and those who acquire skills of <75 are 90% (18 students). In cycle I, after following the Discovery Learning learning model, there was an increase in skills to reach skills > 75 by 40% (8 students) and those who acquired skills of <75 were 60% (12 students). Meanwhile, at the end of cycle II, 85% (17 students) achieved skill >75 and 15 (3 students) obtained skill <75. The average value also increased each cycle. The average gain in the first cycle was 73.80% and in the second cycle it became 80.90%. In other words, class VII students of SMP Negeri 13 Langsa have good skills in ablution skills using the Discovery Learning learning model.